Design and development of an IoT-based archive room security system integrating RFID and fingerprint authentication for military document protection - Tidar, R Haryo; Madramsyah, Adam; Rimbawa, H.A Danang; Sembali, Tryas Putranto (Jurnal Mandiri IT, 2025)
The objective of this research is to design and implement a secure, IoT-based dual-authentication system for protecting classified military archive rooms, in response to the growing urgency of safeguarding sensitive documents against real threats such as espionage, unauthorized access, and data tampering. Military archives store critical information essential for national defense operations, yet many facilities continue to rely on outdated physical security systems vulnerable to intrusion and lacking auditability. This research presents the design and implementation of a dual-authentication archive security system based on Internet of Things (IoT), integrating Radio Frequency Identification (RFID) and fingerprint biometrics. The system is developed using the Waterfall model, involving sequential stages of requirement analysis, system design, implementation, testing, and evaluation. The NodeMCU ESP32 microcontroller serves as the central controller, enabling real-time data transmission via Wi-Fi and notification delivery through the Telegram API. The RFID module performs initial identification, while the fingerprint sensor confirms biometric authentication. A solenoid lock mechanism provides physical access control, activated only upon successful dual verification. System testing under simulated military archive conditions yielded an average response time of 4.59 seconds and an authentication accuracy of 90.6%. Additionally, the real-time notification feature enhanced situational awareness by informing administrators of all access events—both valid and unauthorized. The results indicate that combining RFID and fingerprint authentication significantly improves system security, auditability, and operational efficiency compared to single-factor or conventional methods. This system demonstrates the potential for scalable, adaptable application in high-security institutional environments. Future development may include integration of backup power supplies, encrypted communication protocols, and expansion toward a more comprehensive digital security architecture. This research contributes to the advancement of smart security systems in military infrastructure, promoting proactive threat mitigation and enhanced document protection.